Mechanical Properties of Porcelinite Reinforced Concrete Beams - A. Slaby, Ayad; I. Aziz, Khalil; Farhan Hadeed, Ali (Iraqi Journal of Civil Engineering, 2008)
The researches in Iraq has expanded in the field of material technology involving the properties of the light weight concrete using natural aggregate aviable in westran of Iraq. Researches work on porcelinite concrete has been carried out in several Iraqi Universities. The study is deals with mechanical properties of porcelinite aggregate concrete by casting (273) different specimens. These properties are, compressive strength, flexurale strength, splitting strength, static modulus of elasticity and absorption. The results indicated that the structural light weight aggregate concrete produced from local porcelinite aggregate is suitable to used as a structural concrete, it can produce structural light weight concrete of compressive strength varies from (23.0 to 29.8) MPa with the density ranges from (1745 to 1855) kg/m3, by using cement content about (550 and 650) kg/m3.Such concrete exhibited good mechanical properties. It gave the values of splitting tensile strength, modulus of rupture and modulus of elasticity, 75%, 90% and 60% from those of normal weight concrete respectively owning the same compressive strength and meeting the requirement of ACI-213